Comparison of Green Areas Near Educational Institutions in two districts of Metropolitan Lima, 2019 - Espinoza-Pereyra, Marcos (2020)
The research seeks to establish a comparison between the presence of green areas near educational centers in two districts of Metropolitan Lima, Breña and Pueblo Libre, due to the influence they have on human well-being; the work included field work, with institutional visits to both districts and a cabinet work where the information taken with the Garmin Etrex 20 GPS using Postgresql/Postgis software, besides Google Earth Pro program and the description obtained in the field work was processed. It was determined that Pueblo Libre has a higher percentage of total park area (and consequently, a greater amount of green area), so the relationship of parks with the number of educational entities at radii of 100, 200 and 300 m in Pueblo Free is greater; Breña has 0.33 m2 of green area per inhabitant and Pueblo Libre 2.14 m2.